Analysis of the political discourse in Spain about school failure on Twitter - Jesus Domingo; José Manuel Martos (Arizona State University, 2016)
Political parties incorporate their public profiles on Twitter as a tool of communication and advertising. School failure has been a recurring theme in this policy agenda. The deep understanding of this complex reality requires a critical analysis of the media in which it occurs and conveys. This study characterizes this theme-guidelines and underlying intentions of political discourses about school failure in the accounts of the main Spanish political parties with parliamentary representation. It uses critical discourse analysis and grounded theory as a lens to view media and networks, with Twitter as a particular focus. Paying particular attention to systematize the search and seizure of information so as to avoid the volatility of the content, the results suggested that understanding of school failure does not matter: it is ignored or is used as a weapon to justify the party's policies and to discredit those of others political parties. Discourse on Twitter offers a highly ideological approach to a characterization of school failure from the simplification of the figures and accompanying visions of school failure.